The Influence Of Marketing Strategy and Brand Community On MSME Sales In South Tangerang City - Sam Cay; Jeni Irnawati (Jurnal Pemasaran Kompetitif, 2020)
The purpose of this study was to determine the appropriate marketing strategy to increase sales volume at MSME South Tangerang, to find out which Brand Community could improve purchasing decisions at MSME South Tangerang and to find out marketing strategies and Brand Community that could increase sales at MSME South Tangerang. The method used for this research is the mix methods method. The population in this study is the population of all MSMEs in the South Tangerang area, and the sample we use is the MSMEs who are members of a Tangsel community called Tangsel Berkibar which number more than 500 MSME members. Because the population is too large, namely more than 100 people and limited time and personnel, the number of samples taken by the researcher is 50 respondents in that population. Where according to Arikunto (2002: 112) if the population is more than 100 then 5-10% or 20-30% of the population is taken. The statistical analysis used was the classical assumption test and multiple linear regression using the SPSS 26 program.The results obtained were that there was a partially significant influence between E-commerce Marketing on the Sales of South Tangerang MSMEs, there was a partially significant effect between Brand Community and the Sales of Tangerang MSMEs. South and there is a significant influence simultaneously between E-commerce Marketing and Brand Community on the Sales of South Tangerang MSMEs.